(untitled) (Contemporary Journal of Social Science Review, 2025)
Climate change and water scarcity have emerged as significant threats to Pakistan’s agricultural sector, which is the backbone of the country’s economy and food security. Rising temperatures, unpredictable rainfall patterns, frequent droughts, and glacial melt are affecting crop yields, irrigation systems, and overall agricultural productivity. Water resources, already under stress due to overuse and poor management, are becoming increasingly scarce, exacerbating the challenges faced by farmers. This study explores the interconnected impacts of climate change and water scarcity on agriculture in Pakistan. It also highlights the urgent need for adaptive strategies, sustainable water management, and policy reforms to safeguard the future of agriculture and ensure food security for the growing population.